A preliminary study into injuries due to non-perforating ballistic impacts into soft body armour over the spine - Jennings, Rosalind M.; Malbon, Christopher; Brock, Fiona; Harrisson, Stuart; Carr, Debra J. (Elsevier, 2018)
The UK Home Office test method for ballistic protective police body armours considers anterior torso impacts to be the worst-case scenario and tests rear armour panels to the same standards as front panels. The aim of this paper was to examine the injuries from spinal behind armour blunt trauma (BABT) impacts. This study used a cadaveric 65 kg, female pig barrel and 9 mm Luger ammunition (9 × 19 mm, FMJ Nammo Lapur Oy) into HG1/A + KR1 soft armour panels over the spine. Injuries were inspected and sections removed for x-radiography and micro-CT assessment. All shots over the spine resulted in deep soft tissue injuries from pencilling of the armour and the shirt worn under the armour. The wounds had embedded fabric debris which would require surgery to remove resulting in increased recovery time over injuries usually seen in anterior torso BABT impacts, which are typically haematoma and fractured ribs. The shot with the deepest soft tissue wound (41 mm) also resulted in a fractured spinous process. Shots were also fired at the posterior and anterior rib area of the pig barrel, for comparison to the spine. Similar wounds were seen on the shots to the posterior rib area while shallower, smaller wounds were seen on the anterior and one anterior rib shot resulted in a single, un-displaced rib fracture. The anatomical differences between pigs and humans would most likely mean that injury to a human from these impacts would be more serious.
Keywords: Pencilling; Police; BABT; HG1/A; Spinal Fracture Soft tissue wounds